Scrambling for Cuan? Social Conflict in the Development of Batu Dinding Waterfall Ecotourism - Indrizal, Edi; Ermayanti, Ermayanti; Irwandi, Ade; Nurti, Yevita (Lasigo Akademia Indonesia, 2024)
This paper describes the dynamics of conflict that occurred in the Batu Dinding rural tourism development between the local community and Tanjung Belit Village. The conflict occurred since 2015, and it’s was declared over in 2021. Therefore, what were the dynamics of the conflict during those six years? This research uses a qualitative-descriptive method with data collection through fieldwork. The data collection techniques used were a combination of limited participant observation techniques, informal and semi-structured interviews, and document studies. The results show that the conflict over the management of the Batu Dinding Waterfall tourism area in Tanjung Belit Village originated from agrarian conflicts related to land reoccupation. The motive is motivated by the development of tourism that has economic value and wants to monopolize it to get economic benefits (cuan). So the horizontal conflict between the Domo tribe and Tanjung Belit Village with the Tanjung tribe was resolved through legal channels and the police and the actors who committed acts of violence should also be imprisoned. In the end, the conflict was resolved through inter-tribal deliberation and the land was retained by Tanjung Belit Village.